PENGARUH EDUKASI E-POSTER TERHADAP PENGETAHUAN DAN SIKAP TERKAIT NYERI MUSKULOSKELETAL PADA CALON JEMAAH HAJI DI KOTA BATU - Khansa Fitrah Shaliha; Shelly Taurhesia; Greesty Finotory Swandiny (Faculty of Pharmacy, Universitas Pancasila, 2025)
Excessive free radicals accelerate skin degradation by causing oxidative damage to keratinocytes and fibroblasts, leading to structural protein breakdown (collagen, elastin, keratin), lipid peroxidation, and DNA damage. This process compromises skin barrier integrity, reduces elasticity, and promotes premature aging. Antioxidants play a crucial role in protecting the skin by neutralizing reactive oxygen species (ROS) and preventing lipid peroxidation. This study aimed to develop a topical cream containing jujube (Ziziphus mauritiana L.) and perilla (Perilla frutescens L. Britton) leaf extracts and evaluate its antioxidant activity and dermal safety. Extracts were obtained through kinetic maceration using 70% ethanol and formulated into oil-in-water creams at two concentration levels. The creams were assessed for physical characteristics (organoleptic properties, cream type, pH, homogeneity, spreadability, rheology, viscosity), stability under room and accelerated conditions (40°C for 4 weeks), antioxidant activity via DPPH assay, and irritation potential using albino rabbits. All formulations exhibited good physical properties, stability, and homogeneity. Irritation testing showed no erythema or edema, confirming the cream’s safety for topical application. Antioxidant testing revealed strong free radical scavenging activity, with IC50 values of 119.705 ppm (F1) and 66.938 ppm (F2). Accelerated storage slightly reduced antioxidant activity, while higher extract concentrations enhanced antioxidant effects compared to the base formulation. These findings indicate that jujube (Ziziphus mauritiana L.) and perilla (Perilla frutescens L. Britton) leaf extracts synergistically enhance antioxidant activity in a safe topical cream formulation, demonstrating potential as a natural preparation for skin protection against oxidative damage.